Nano-scale high-entropy A2B2O7 type oxide ceramic powder and preparation method of nano ceramic block of nano-scale high-entropy A2B2O7 type oxide ceramic powder
Nano-level high-entropy A2B2O7 oxide powder was prepared by sol-gel method, and discharge plasma technology combined with two-step sintering process was used to solve the problem of reducing structural and chemical stability of ceramics under high irradiation environments, realizing the material Improved high-efficiency thermal protection and radiation resistance.
Patent Information
- Application Number
- CN202411650949.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
In practical applications, A2B2O7 oxide ceramics have problems such as unsatisfactory thermal cycle life and reduced structural stability and chemical stability in high irradiation environments.
The nano-level high-entropy A2B2O7 oxide powder was prepared by sol-gel method, and a high-density grain boundary was formed by discharging plasma technology combined with a two-step sintering process to improve the thermal conductivity and radiation resistance of the material.
It significantly improves the thermal protection and radiation resistance of the material, enhances chemical stability, and meets the requirements of high radioactive waste curing.
Smart Images

Figure CN119462182A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano-ceramics, and in particular to a method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof. Background Art
[0002] A2B2O7 oxides are a type of structural ceramic material with strong structural tolerance and flexible composition control. Ra2Zr2O7 oxides, where A is a rare earth element (Ra) and B is a Zr element, have the advantages of high melting point, low thermal conductivity, and low oxygen permeability, and are important candidate materials in the field of thermal barrier coatings. At the same time, they have excellent radiation resistance and high chemical stability, and also have potential application value in the field of high-level radioactive waste solidification.
[0003] Although A2B2O7 oxide ceramics have many advantages, they also have some shortcomings that need to be improved. For example, La2Zr2O7 ceramics have relatively low thermal expansion coefficients (9.1×10–6K–1, 1000℃) and fracture toughness (1.4MPa·m1 / 2), resulting in unsatisfactory thermal cycle life of the coating. In addition, as a solidified substrate, it still cannot meet the requirements of long-term geological disposal. Under strong irradiation of plutonium and plutonium-containing waste or α-containing waste, the crystal structure will undergo devitrification, which greatly reduces its structural stability and chemical stability, leading to nuclide leakage. Therefore, the performance of A2B2O7 oxide ceramics needs to be further improved before they can be actually used in thermal barrier coatings and high-level radioactive waste solidification.
[0004] To address the above problems, we have introduced a method for preparing nanoscale high-entropy A2B2O7-type oxide ceramic powder and its nanoceramic blocks. Summary of the invention
[0005] The invention discloses a preparation method of a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof, aiming to solve the technical problems in the background technology.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder comprises the following steps:
[0008] S1. Evenly dispersing a rare earth element source and a transition metal source in deionized water, stirring at room temperature, and then adding a polymerizing agent and an inducing agent to obtain a mixed solution;
[0009] S2, continue stirring at room temperature to form a transparent clear solution;
[0010] S3, heating the transparent clear solution until a milky white gel is gradually formed;
[0011] S4. Dry the milky white gel into a dry gel, sinter it at 800° C. for 5 hours, and grind it to obtain a nano-scale A2B2O7 type high entropy oxide powder material.
[0012] The rare earth element source in step S1 may be one of the following:
[0013] La3+, Sm3+, Gd3+, Dy3+, Eu3+;
[0014] La3+, Pr3+, Sm3+, Gd3+, Nd3+, Eu3+;
[0015] The transition metal element source is Zr4+.
[0016] The rare earth element source in step S1 may be one of the following:
[0017] La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Eu(NO3)3·6H2O;
[0018] La(NO3)3·6H2O, Pr(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Nd(NO3)3·6H2O, Eu(NO3)3·6H2O;
[0019] The transition metal element source is ZrO(NO3)2·xH2O.
[0020] The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to deionized water is 0.2-0.24 mol:1L.
[0021] The ratio of the total molar amount of the rare earth element source to the total molar amount of the transition metal element source is 1:1±0.1, and the molar amount of each rare earth element in the rare earth element source is equal.
[0022] The polymerization agent is acrylamide and N,N-methylenebisacrylamide, and the inducing agent is ammonium persulfate.
[0023] The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to the molar amount of acrylamide is 1:30;
[0024] The molar ratio of acrylamide to N,N-methylenebisacrylamide is 10:1;
[0025] The molar ratio of acrylamide to ammonium persulfate is 20:1.
[0026] A method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic block comprises the following steps:
[0027] The ground nano-scale A2B2O7 high entropy oxide powder material is sieved through a 300-mesh sieve;
[0028] The sieved nano-scale A2B2O7 high entropy oxide powder material is loaded into a graphite mold for two-step spark plasma sintering, firstly vacuum sintering at 30 MPa and 1500°C for 3 min, and then vacuum sintering at 30 MPa and 1400°C for 1 min to obtain nano-scale A2B2O7 high entropy oxide ceramics.
[0029] The method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof provided by the present invention has the following advantages:
[0030] 1. The present invention uses the pyrochlore structure of Gd2Zr2O7 as a matrix, adopts a sol-gel method, introduces 4 to 5 rare earth elements into the Gd2Zr2O7 structure, obtains a high-entropy oxide powder material with an average powder particle size of less than 25 nm, and completes the preparation of a high-entropy oxide ceramic block with an average grain size of less than 75 nm through discharge plasma technology combined with a two-step sintering process.
[0031] 2. The present invention uses discharge plasma technology combined with a two-step sintering process to prepare a high-entropy nano-ceramic block, which introduces a large number of high-density grain boundaries into the material, which greatly increases phonon scattering, further reduces the thermal conductivity of the material, and makes the thermal protection performance more excellent. At the same time, the high-density grain boundaries act as "defect traps" that capture defects, absorbing radiation defects, making the material have more excellent radiation resistance, and it has important value as a high-level radioactive waste solidification substrate.
[0032] 3. The present invention introduces a large amount of rare earth elements into the pyrochlore structure of Gd2Zr2O7 to complete the design and preparation of the A2B2O7 type oxide high entropy structure. Due to the difference in the radius of the cations, the internal structure of the material crystal undergoes obvious lattice distortion, which also increases phonon scattering and reduces the thermal conductivity of the material. At the same time, it also causes ion diffusion hysteresis, increases atomic migration energy and diffusion energy, and is difficult to form defects such as out-of-position atoms and vacancies. Moreover, defects are difficult to aggregate to form large-sized defects, and have excellent radiation resistance. The chemical stability of this high-entropy oxide material is also greatly improved.
[0033] 4. The present invention selects rare earth elements La, Pr, Sm, Gd, Dy, Eu, Nd, and transition metal element Zr as components of high entropy oxides. When each element exists alone as an oxide, it has excellent properties such as high thermal stability, good mechanical properties, corrosion resistance, stable chemical properties, and radiation resistance. In addition, the nanoscale high entropy oxide synthesized by the present invention has further improved mechanical properties, physical properties, chemical properties, etc.
[0034] 5. The present invention uses the sol-gel method to synthesize high entropy oxide powder materials. The oxide synthesized by this method has the characteristics of fine powder particle size, uniform distribution and few impurities. In addition, this method has a low synthesis temperature and low cost.
[0035] 6. The present invention adopts a two-step preparation process combined with spark plasma sintering, which has high efficiency and dense sintering, can control the grain size of ceramic block materials, and complete the preparation of high-quality nano-scale ceramic blocks with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention provides a powder preparation flow chart for a method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof.
[0037] Figure 2 This is a block preparation flow chart of a method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof proposed by the present invention.
[0038] Figure 3 This is a physical photo of the preparation method of a nano-scale high-entropy A2B2O7 type oxide ceramic powder and its nano-ceramic block proposed by the present invention.
[0039] Figure 4 The scanning electron microscope images of the nano-scale high entropy oxide powders prepared in Examples 1 and 2 of the present invention are shown in Figure a. The scanning electron microscope image of the nano-scale high entropy oxide powders of Example 1 is shown in Figure b. The scanning electron microscope image of the nano-scale high entropy oxide powders of Example 2 is shown in Figure d.
[0040] Figure 5 The X-ray diffraction patterns of the nanoscale high entropy oxide powders prepared in Examples 1 and 2 of the present invention are shown in Figure a. The X-ray diffraction pattern of the nanoscale high entropy oxide powder of Example 1 is shown in Figure b. The X-ray diffraction pattern of the nanoscale high entropy oxide powder of Example 2 is shown in Figure a.
[0041] Figure 6 This is a photograph of a sample of a high entropy oxide nanoscale solidified substrate prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application usually described and marked in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.
[0043] The invention discloses a method for preparing a nano-scale high-entropy A2B2O7 type oxide ceramic powder and a nano-ceramic block thereof.
[0044] Example 1
[0045] Rare earth element sources La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Eu(NO3)3·6H2O and transition metal element source ZrO(NO3)2·xH2O were uniformly dispersed in deionized water to prepare a homogeneous solution with a concentration of 0.2 mol / L. Among them, the molar ratio of La3+, Sm3+, Gd3+, Dy3+ and Eu3+ was 1:1:1:1:1, and the total molar ratio of the metal elements of the rare earth element source to the total molar ratio of the metal elements of the transition metal element source was 1:1±0.1. Then, the stirring treatment was carried out at room temperature with a stirring speed of 200 rpm. Then, during the stirring process, a polymerizer (acrylamide and N,N-methylenebisacrylamide) and an inducing agent (ammonium persulfate) are added to obtain a mixed solution; wherein, the molar ratio of the total metal cations of the rare earth element source and the transition metal element source to the molar ratio of acrylamide is 1:30; the molar ratio of acrylamide to N,N-methylenebisacrylamide is 10:1; and the molar ratio of acrylamide to ammonium persulfate is 20:1. Impurities introduced by acrylamide, N,N-methylenebisacrylamide and ammonium persulfate can be removed in the subsequent sintering process. At room temperature, the mixed solution is continuously stirred until it is clear and transparent, and then the temperature is gradually increased until the solution gradually becomes a milky white gel, at which point heating and stirring are stopped. Subsequently, the dry gel is dried at 150°C for 48 hours to form a dry gel, and the dry gel is sintered at 800°C for 5 hours to obtain a high entropy oxide powder material with a powder particle size of less than 25nm.
[0046] Example 2
[0047] Rare earth element sources La(NO3)3·6H2O, Pr(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Nd(NO3)3·6H2O, Eu(NO3)3·6H2O and transition metal element source ZrO(NO3)2·xH2O were uniformly dispersed in deionized water to prepare a homogeneous solution with a concentration of 0.24 mol / L, wherein the molar ratio of La3+, Pr3+, Sm3+, Gd3+, Nd3+ and Eu3+ was 1:1:1:1:1:1, and the total molar ratio of the metal elements of the rare earth element source to the total molar ratio of the metal elements of the transition metal element source was 1:1±0.1. The solution was then stirred at room temperature at a speed of 200 rpm. Then, during the stirring process, a polymerizer (acrylamide and N,N-methylenebisacrylamide) and an inducing agent (ammonium persulfate) are added to obtain a mixed solution; wherein, the molar ratio of the total metal cations of the rare earth element source and the transition metal element source to the molar ratio of acrylamide is 1:30; the molar ratio of acrylamide to N,N-methylenebisacrylamide is 10:1; and the molar ratio of acrylamide to ammonium persulfate is 20:1. Impurities introduced by acrylamide, N,N-methylenebisacrylamide and ammonium persulfate can be removed in the subsequent sintering process. At room temperature, the mixed solution is continuously stirred until it is clear and transparent, and then the temperature is gradually increased until the solution gradually becomes a milky white gel, at which point heating and stirring are stopped. Subsequently, the dry gel is dried at 150°C for 48 hours to form a dry gel, and the dry gel is sintered at 800°C for 5 hours to obtain a high entropy oxide powder material with a powder particle size of less than 25nm.
[0048] Example 3
[0049] The nano-scale high entropy oxide powder material of Example 1 or Example 2 is ground and sieved. In this embodiment, an agate mortar is used for grinding, and a 300-mesh sieve is used for sieving. The nano-scale high entropy oxide powder is loaded into a graphite mold with a diameter of 25 mm and pressurized to 30 MPa at 3 MPa / min. Using spark plasma sintering technology, under vacuum conditions, the first step is to heat up to 1500°C at 500°C / min and keep warm for 3 minutes; the second step is to cool down to 1400°C at 100°C / min, keep warm for 1 minute, and then cool down to 600°C at 200°C / min. Finally, a high-entropy oxide ceramic block with a grain size of less than 75nm is obtained.
[0050] The performance of the nanoscale high entropy oxide powder material and the nanoscale solidified substrate prepared in the above examples is tested below.
[0051] 1. Powder photos
[0052] The actual photos of the nano-scale high entropy oxide powder materials prepared in Examples 1 and 2 of the present invention are as follows: Figure 3 As shown. Among them, Figure 3 Figure a is a physical photograph of the high entropy oxide powder of Example 1; Figure 3 Figure b is a physical photograph of the high entropy oxide powder of Example 2.
[0053] Depend on Figure 3 It can be seen that the nanoscale high entropy oxide powders synthesized in Example 1 and Example 2 of the present invention have different colors, and the colors of the powders are different due to the different types of rare earth elements.
[0054] 2. X-ray diffraction test
[0055] The nano-scale high entropy oxide powders prepared in Example 1 and Example 2 of the present invention were subjected to X-ray diffraction tests, and the results are as follows: Figure 4 shown. Figure 4 Figure a is the X-ray diffraction pattern of the high entropy oxide powder of Example 1; Figure 4 Figure b is the X-ray diffraction pattern of the high entropy oxide powder of Example 2.
[0056] Depend on Figure 4 It can be seen that the physical phases of the nano-scale high entropy oxide powders prepared in Example 1 and Example 2 of the present invention are both typical A2B2O7 structures.
[0057] 3. Scanning electron microscope test
[0058] The product obtained by the embodiment of the present invention was tested by scanning electron microscope, and the results are as follows: Figure 5 and Figure 6 shown. Figure 5 Figure a is a secondary electron scanning electron microscope photograph of the nanoscale high entropy oxide powder of Example 1; Figure 5 Figure b is a scanning electron microscope secondary electron photograph of the nanoscale high entropy oxide powder of Example 2. Figure 6 Figure a is a secondary electron micrograph of the nanoscale solidified substrate of Example 3 using a scanning electron microscope; Figure 6 Figure b is a scanning electron microscope backscattered photograph of the cured substrate of Example 8.
[0059] Depend on Figure 5 It can be seen that the high entropy oxide powders prepared in Examples 1 and 2 of the present invention are fine and uniform, with an average grain size of about 30 nm. Figure 6 It can be seen that the high entropy oxide solidified body substrate prepared in Example 3 of the present invention is dense, has a low porosity, and has a uniform grain size of about 70 nm.
[0060] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. The replacement may be a replacement of a part of the structure, device, method step, or a complete technical solution. Any equivalent replacement or change according to the technical solution and the inventive concept of the present invention shall be covered within the protection scope of the present invention.
Claims
1. A method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder, characterized in that: The following steps are involved: S1. Evenly dispersing a rare earth element source and a transition metal source in deionized water, stirring at room temperature, and then adding a polymerizing agent and an inducing agent to obtain a mixed solution; S2, continue stirring at room temperature to form a transparent clear solution; S3, heating the transparent clear solution until a milky white gel is gradually formed; S4. Dry the milky white gel into a dry gel, sinter it at 800° C. for 5 hours, and grind it to obtain a nano-scale A2B2O7 type high entropy oxide powder material.
2. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The rare earth element source in step S1 may be one of the following: La3+, Sm3+, Gd3+, Dy3+, Eu3+; La3+, Pr3+, Sm3+, Gd3+, Nd3+, Eu3+; The transition metal element source is Zr4+.
3. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The rare earth element source in step S1 may be one of the following: La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, Eu(NO3)3·6H2O; La(NO3)3·6H2O, Pr(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Nd(NO3)3·6H2O, Eu(NO3)3·6H2O; The transition metal element source is ZrO(NO3)2·xH2O.
4. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to deionized water is 0.2-0.24 mol:1L.
5. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The ratio of the total molar amount of the rare earth element source to the total molar amount of the transition metal element source is 1:1±0.1, and the molar amount of each rare earth element in the rare earth element source is equal.
6. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The polymerization agent is acrylamide and N,N-methylenebisacrylamide, and the inducing agent is ammonium persulfate.
7. The method for preparing nano-scale high entropy A2B2O7 type oxide ceramic powder according to claim 1, characterized in that: The ratio of the total molar amount of metal cations of the rare earth element source and the transition metal element source to the molar amount of acrylamide is 1:30; The molar ratio of acrylamide to N,N-methylenebisacrylamide is 10:1; The molar ratio of acrylamide to ammonium persulfate is 20:
1.
8. A method for preparing a nano-scale high entropy A2B2O7 type oxide ceramic block according to claims 1-7, characterized in that: The following steps are involved: a. Sieve the ground nano-scale A2B2O7 high entropy oxide powder material through a 300-mesh sieve; b. The sieved nano-scale A2B2O7 high-entropy oxide powder material is loaded into a graphite mold for two-step spark plasma sintering, first vacuum sintering at 30 MPa and 1500°C for 3 min, and then vacuum sintering at 30 MPa and 1400°C for 1 min to obtain nano-scale A2B2O7 high-entropy oxide ceramics.
Citation Information
Cited By
Rare-earth-based medium-entropy ceramic with high oxygen mobility and preparation method of rare-earth-based medium-entropy ceramic
CN120841956A
Pyrochlore structure high-entropy ceramic solidified body material as well as preparation method and application thereof
CN121405463A
Hafnium europium oxide neutron absorption ceramic material, preparation method and application thereof
CN122301551A